Perfluorocarbon nanodrug induced oxygen self-enriching sonodynamic therapy improves cancer immunotherapy after insufficient radiofrequency ablation - Huang, Tongyi; Wu, Wenxin; Wu, Jiancong; Tan, Yang; Zhang, Minru; Long, Haiyi; Guo, Huanling; Zhang, Xiaoer; Zhou, Wenwen; Zhang, Qi; Xie, Xiaoyan; Xu, Ming; et al. (Frontiers in Immunology, 2023)
Residual lesions and undetectable metastasis after insufficient radiofrequency ablation (iRFA) are associated with earlier new metastases and poor survival in cancer patients, for induced aggressive tumor phenotype and immunosuppression. Programmed cell death protein 1(PD-1) blockade has been reported to enhance the radiofrequency ablation-elicited antitumor immunity, but its ability to eliminate incompletely ablated residual lesions has been questioned. Here, we report a combined treatment modality post iRFA based on integrating an oxygen self-enriching nanodrug PFH-Ce6 liposome@O2 nanodroplets (PCL@O2)-augmented noninvasive sonodynamic therapy (SDT) with PD-1 blockade. PCL@O2 containing Ce6 as the sonosensitizer and PFH as O2 reservoir, was synthesized as an augmented SDT nanoplatform and showed increased ROS generation to raise effective apoptosis of tumor cells, which also exposed more calreticulin to induce stronger immunogenic cell death (ICD). Combining with PD-1 blockade post iRFA, this optimized SDT induced a better anti-tumor response in MC38 tumor bearing mouse model, which not only arrested residual primary tumor progression, but also inhibited the growth of distant tumor, therefore prolonging the survival. Profiling of immune populations within the tumor draining lymph nodes and tumors further revealed that combination therapy effectively induced ICD, and promoted the maturation of dendritic cells, tumor infiltration of T cells, as well as activation of cytotoxic T lymphocytes. While iRFA alone could result in an increase of regulatory T cells (Tregs) in the residual tumors, SDT plus PD-1 blockade post iRFA reduced the number of Tregs in both primary and distant tumors. Moreover, the combined treatment could significantly initiate long-term immune memory, manifesting as elevated levels of CD8+ and CD4+ central memory cells. Therefore, this study establishes the preclinical proof of concept to apply oxygen self-enriching SDT to augment cancer immunotherapy after iRFA.